WEBVTT
00:00:02.590 --> 00:00:11.560
Solve π₯ plus six is equal to π to the power of ln π₯ squared for π₯, giving your answer to three decimal places.
00:00:12.610 --> 00:00:20.240
Well, to start to solve this problem, the first thing we look at is this term here, which is π to the power of ln π₯ squared.
00:00:21.260 --> 00:00:28.100
To understand what this term will become, what Iβm gonna do is Iβm going to say that π¦ is equal to π to the power of ln π₯ squared.
00:00:29.500 --> 00:00:34.370
Itβs worth noting that you may also here ln called ln or natural logarithm.
00:00:34.680 --> 00:00:37.230
But just for this video, Iβm actually gonna say ln.
00:00:37.790 --> 00:00:42.420
Okay, so the first thing weβre gonna do is actually take the natural logarithm of each side.
00:00:43.130 --> 00:00:48.690
So itβs gonna give me that ln π¦ is equal to ln π to the power of ln π₯ squared.
00:00:49.680 --> 00:00:56.150
And then next, we will apply a log rule that says that ln π to the power of π₯ is equal to π₯ ln π.
00:00:57.080 --> 00:01:02.540
And this gonna give us that ln π¦ equals ln π₯ squared multiplied by ln π.
00:01:03.910 --> 00:01:09.590
And then, weβre gonna use a relationship that we know which is that ln π is equal to one.
00:01:11.410 --> 00:01:20.390
So therefore, weβre left with ln π¦ is equal to ln π₯ squared because it will be ln π₯ squared multiplied by one, which just gives us ln π₯ squared.
00:01:21.650 --> 00:01:23.570
And then, we have that π¦ is equal to π₯ squared.
00:01:23.920 --> 00:01:28.990
And we know that because actually we have a log to the same base of both sides for equation.
00:01:29.510 --> 00:01:31.590
Okay, great, so why is this useful?
00:01:32.580 --> 00:01:39.400
Well, itβs useful because actually we know that π¦ β looking back to the beginning β was equal to π to the power of ln π₯ squared.
00:01:39.720 --> 00:01:45.360
So therefore, we can say that π to the power of ln π₯ squared is just equal to π₯ squared.
00:01:46.700 --> 00:01:56.750
Okay, great, what I can actually do now is look back to our equation and we can actually apply this relationship and substitute π₯ squared for π to the power of ln π₯ squared.
00:01:57.440 --> 00:02:00.590
So therefore, we have π₯ plus six is equal to π₯ squared.
00:02:01.940 --> 00:02:05.130
So now, what we do is we actually rearrange to set all equal to zero.
00:02:05.470 --> 00:02:08.480
So what Iβve actually done is actually subtracted π₯ and six from each side.
00:02:08.480 --> 00:02:12.770
So we get zero is equal to π₯ squared minus π₯ minus six.
00:02:13.740 --> 00:02:18.040
So then, weβre actually gonna solve our quadratic and weβre gonna solve it using factoring.
00:02:18.400 --> 00:02:24.060
So if we factor it, we get zero is equal to π₯ minus three multiplied by π₯ plus two.
00:02:25.670 --> 00:02:31.660
And we get this factor because negative three multiplied by two is equal to negative six.
00:02:31.660 --> 00:02:36.670
And thatβs correct because thatβs what it should equal because it should equal the final term of our quadratic.
00:02:37.630 --> 00:02:41.420
And then, we have negative three plus two is equal to negative one.
00:02:41.420 --> 00:02:44.750
And thatβs correct because thatβs actually the coefficient of our π₯ term.
00:02:45.700 --> 00:02:46.730
So great, theyβre both checked.
00:02:46.730 --> 00:02:48.760
So yeah, theyβre definitely the correct factors.
00:02:49.140 --> 00:02:50.440
Okay, so we can now solve.
00:02:51.350 --> 00:03:03.490
And in order to find our π₯-values at this point, what we actually want to do is to set each of our parentheses to zero because if the answer of the equation is zero, then at least one of our parentheses will also have to be zero to achieve this.
00:03:03.740 --> 00:03:07.170
So first of all, we will start with π₯ minus three is equal to zero.
00:03:08.090 --> 00:03:10.870
So therefore, if we add three to each side, we get that π₯ is equal to three.
00:03:10.920 --> 00:03:13.160
So great, thatβs one of our solutions.
00:03:14.070 --> 00:03:21.270
And then, if we have π₯ plus two is equal to zero, if we subtract two from each side, we will be left with π₯ is equal to negative two.
00:03:21.270 --> 00:03:22.340
So thatβs our other solution.
00:03:23.400 --> 00:03:35.410
So therefore, we can say that solutions to π₯ plus six is equal to π to the power of ln π₯ squared for π₯ are π₯ is equal to three or π₯ is equal to negative two.